2011
DOI: 10.1111/j.1439-0418.2011.01654.x
|View full text |Cite
|
Sign up to set email alerts
|

Are primary woody hosts ‘island refuges’ for host‐alternating aphids and important for colonization of local cereals?

Abstract: Only few studies are available dealing with the relation between winter host density and spatial distribution and spring colonization of winter cereals by the host-alternating cereal aphid species Rhopalosiphum padi and Metopolophium dirhodum. Large-scale studies in climatically different agroecosystems in Germany from 2004 to 2006 revealed for R. padi and M. dirhodum larger spring/summer populations in landscapes with higher densities of winter hosts. A small-scale study was performed in winter wheat fields a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…A study showed that the aphid clones on the winter host plant did not significantly contribute to the spring/summer population build-up in the cereal fields over short distances, but that the density of sources for early migrants, on a regional scale, is important for the establishment of the population [67] . Therefore, the migration of aphids plays an important role in genetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the aphid clones on the winter host plant did not significantly contribute to the spring/summer population build-up in the cereal fields over short distances, but that the density of sources for early migrants, on a regional scale, is important for the establishment of the population [67] . Therefore, the migration of aphids plays an important role in genetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…Many unique alate clones with high genetic diversity could still potentially colonize a secondary host field but would be difficult to detect because clonal amplification only favors those with the highest reproductive output. In Klueken et al (2011), secondary host colonizers from the primary plant source had a R of 0.96, and the earliest aphid populations on the secondary host had a R of 1.0, suggesting high initial genotypic diversity during secondary host colonization. Selection could be in the form of plant quality (Noma et al, 2010), insecticidal seed treatments (Magalhaes et al, 2009), soybean variety or other characteristics related to common agronomic practices.…”
Section: Heterozygosity Excessmentioning
confidence: 99%
“…However, in some cases, especially with late populations, genotypic diversities were close or at maximum, that is, every individual was represented by a different clonal genotype. In these instances, we also included common population genetic statistics used in previous aphid genetic studies (Miller et al, 2003;Vialatte et al, 2005;Klueken et al, 2011), as data mirrored randomly admixed populations atypical of clonal reproduction. The probability of two individuals that share a MLG (that is, clones) resulting from a sexual reproduction event was calculated using P sex using GenClone (ArnaudHaond et al, 2007).…”
Section: Polymorphism and Genetic Diversity Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the species is regarded as an intensively spreading invasive alien that has the ability to form monospecific stands in nature (Starfinger et al 2003). The recent study by Klueken et al (2012) demonstrated that the colonization of summer hosts by R. padi depends on the density of winter hosts which are a source of early season migrants. It is likely that the increasing abundance of P. serotina may contribute to the bird cherry-oat aphid population build-up in the adjacent cereal crops.…”
Section: Introductionmentioning
confidence: 99%